PROFIL PEMBELAJARAN KELAS VIII PADA ERA PANDEMI COVID-19 DI SMP NASIONAL BANAU KOTA TERNATE - Ayu Utami Sillia; Chumidach Roini; Abdu Mas'ud (JURNAL BIOEDUKASI, 2022)
The Covid-19 pandemic that is sweeping the world is currently forcing people to stay at home so that they can no longer do activities outside the home as usual, including studying at school, doing the learning process as usual, while efforts to educate the nation's life must be done in an innovative way, one of which is by doing the online learning process. This study aims (1) to reveal the profile of class VIII biology learning in the era of the Covid-19 pandemic, (2) To find out the constraints of class VIII biology learning in the era of the Covid-19 pandemic. The type of research used is qualitative descriptive using observations, interviews and documentation. The results of this study showed that it was explained at the planning, implementation and evaluation stage carried out by teachers in the field of Biology IPA studies, namely, at the stage of learning planning conducted offline (face-to-face) with teaching materials in the form of RPP, Syllabus, LKS and package books, while at the stage of the implementation and evaluation process through online learning. From the tendency of planning is not in accordance with the implementation of learning because, planning through offline (face-to-face) while the implementation is online (online).